Fun Thinkers Book Based on a Contextual Approach to Improve Science Learning Outcomes of Third-Grade Elementary School Students - Yuli, Ni Kadek; I Gusti Ayu Tri Agustiana; Putu Rahayu Ujianti (Universitas Pendidikan Ganesha, 2025)
The low learning outcomes of students in IPAS subjects in the third grade of elementary school, particularly in the material on the life cycle of living things, is the main focus of this study. This study aims to develop and test the effectiveness of the Fun Thinkers Book, a context-based learning tool, as an educational aid to improve student learning outcomes. The research design employed is a Research and Development (R&D) study using the ADDIE model, which consists of the following stages: Analyze, Design, Development, Implementation, and Evaluation. The research subjects include one class of third-grade students. Data collection techniques were conducted through questionnaires and documentation of learning outcomes, using instruments such as expert validation questionnaires and learning outcome tests. Data were analyzed using descriptive qualitative and quantitative approaches. The results of the study indicate that the use of the Fun Thinkers Book significantly improves students' IPAS learning outcomes. This media proved effective in presenting material in a contextual and engaging manner, as well as encouraging active student participation during the learning process. This study concluded that the Fun Thinkers Book media, based on a contextual approach, is suitable and effective for supporting improvements in student learning outcomes in IPAS. Implicitly, this media can serve as an innovative learning strategy alternative in creating a more meaningful and enjoyable learning environment.